A putative proline-rich protein of B. napus - Namasivayam, Parameswari; Hanke, David (Universiti Putra Malaysia, 2008)
Proline-rich proteins are among the major protein components of plant cell walls. So far, two different proline-rich cell wall proteins have been described in Brassica napus. This paper reports a study on expression and sequence analysis of a novel class of a proline-rich putative protein, tentatively designated Ae4. The largest ORF of Ae4 encodes 166 amino acid residues without the start and stop codons. Ae4 is a partial length cDNA. The Ae4 gene expression was investigated and the results demonstrate that it accumulates in all vegetative tissues tested as well as in the embryogenic culture of Brassica napus. However, expression of Ae4 was undetectable in the non-embryogenic and cytokinin-treated embryogenic tissues. These results indicate that the Ae4 gene might play a role in somatic embryo formation.